2020
DOI: 10.3389/fonc.2020.01498
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Gene Expression and Cytokine Secretion Is Reduced Among African American Colon Cancer Patients

Abstract: Background: Colorectal cancer is the third most deadly cancer among African Americans (AA). When compared to Caucasian Americans (CA), AA present with more advanced disease and lower survival rates. Here, we investigated if differences in tumor immunology could be contributive to disparities observed between these populations. Methods: We examined gene expression of tumor and non-tumor adjacent tissues from AA and CA by whole transcriptome sequencing, and generated scores for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 29 publications
3
43
0
Order By: Relevance
“…Lower cytotoxic or effector T cell responses in CRCs of AAs vs. CAs have been observed in a few previous studies in colorectal cancers (16)(17)(18)(19). Basa et al (18) identified lower protein expression of granzyme B in CRCs of AAs compared to CAs.…”
Section: Discussionmentioning
confidence: 85%
“…Lower cytotoxic or effector T cell responses in CRCs of AAs vs. CAs have been observed in a few previous studies in colorectal cancers (16)(17)(18)(19). Basa et al (18) identified lower protein expression of granzyme B in CRCs of AAs compared to CAs.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the differences between the two groups studied were also evident in the patterns of cytokine production in plasma. This work indicated the dissimilarities in colon cancer immune characteristics between AA and CA that may be implicated in insufficiency of proper immune defense mechanisms (47).…”
Section: Cancer Transcriptomicsmentioning
confidence: 81%
“…The characteristics of the patients for the subset of samples analyzed compared to that of the total collection of archived sporadic CRC samples (2010-2020) are shown in Table 2 . Since the samples in the subset were originally selected to provide Black/AA samples and “matched” White/EA samples for another transcriptomic profiling performed at a separate sequencing facility[ 25 ], there was significantly higher representation of Black/AA samples in this pilot study. Left-sided CRCs were also more highly represented in the subset compared to the overall collection.…”
Section: Resultsmentioning
confidence: 99%
“…Illumina paired-end sequencing was performed on the Miseq platform with versions v2.4 of the Miseq Control Software and of MiSeq Reporter, using a 600-cycle version 3 reagent kit. Illumina Miseq paired-end reads were aligned to human reference genome hg19 with bowtie2 and matching sequences were discarded as previously described[ 25 ]. All de-multiplexed, paired-end 16S rRNA gene sequence files along with associated metadata were deposited into the Gene Expression Omnibus under project accession number GSE165255.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation